Step aside, pops : a Hark! A vagrant collection - Beaton, Kate, 1983- (Drawn & Quarterly, 2015)
"Ida B. Wells, the Black Prince, and Benito Juárez burst off the pages of Step Aside, Pops: A Hark! A Vagrant Collection, armed with modern-sounding quips and amusingly on-point repartee. Kate Beaton's second D+Q book brings her hysterically funny gaze to bear on these and even more historical, literary, and contemporary figures. Irreverently funny and carefully researched, no target is safe from Beaton's incisive wit in these satirical strips"--